Effects of low-GI biscuits as pre-loads or mid-meal snacks on post-prandial glycemic excursions in women with recent gestational diabetes: A protocol for a randomized crossover trial and an extended tailored intervention - Li, Chunrong; Gao, Yan; Luo, Tongyong; Qin, Shiji; Yao, Xue; Wen, Ye; Wang, Xue; Zhang, Jing; Zhong, Qiong; Shi, Hao; Liu, Jing (Frontiers in Nutrition, 2023)
Background: Increased postprandial glycaemic fluctuations contribute to the development of diabetes and have been observed in women with recent gestational diabetes (GDM) and with normal glucose tolerance at postpartum. However, there is little evidence on diminishing postprandial glycaemic fluctuations by tailored dietary intervention in such population. The primary objective of this proposed trial is to compare the impact of low GI biscuits (Fitmeal) consumed as preload foods or mid-meal snacks by women with recent GDM on postprandial glycemic response (PGR) of a following main meal, comparing with the co-ingestion counterpart and reference meal. The secondary objective is to evaluate effects of the extended tailored intervention either with preloads or mid-meal snacks on glycaemic excursions, self-management behaviors and psychosocial factors. Methods: In a randomized crossover trial, 52 postpartum women with recent GDM will be allocated to four meals: (1) Fitmeal preload and standard lunch meal (P+L), (2) Fitmeal as mid-meal snack and standard lunch meal (S+L), (3) co-ingestion of Fitmeal with standard lunch meal (CL), and (4) standard lunch meal as reference (W+L), on four consecutive days. Acute PGR measured by continuous glucose monitoring (CGM) will be compared among the four meals. And then all participants will receive a 4-week tailored intervention using Fitmeal as preloads or mid-meal snacks based on within-subject PGR results. Glycaemic measurements, health-related behaviors and psychosocial factors will be examined at baseline and end point. Discussion: To our knowledge, this is the first dietary intervention trial, which includes both the evaluation of different dietary strategies on improving postprandial glucose excursions by a randomized crossover design in the first stage and a 4-week tailored dietary intervention followed in the second stage. Findings of this study are expected to guide future clinical practice in medical nutrition therapy for diabetes prevention in postpartum women with recent GDM and also to provide novel information on how to deliver an individualized dietary intervention effectively in the shortest possible time for facilitating long-term compliance to specific dietary intervention related to prevent diabetes.